2020
DOI: 10.3348/kjr.2019.0820
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urologist Satisfaction for Different Types of Prostate MRI Reports: A Large Sample Investigation

Abstract: Objective: To evaluate urologist satisfaction on structured prostate MRI reports, including report with tumor-node-metastasis (TNM) staging (report B) and with Prostate Imaging Reporting and Data System (PI-RADS) score with/without TNM staging (report C, report with PI-RADS score only [report C-a] and report with PI-RADS score and TNM staging [C-b]) compared with conventional free-text report (report A). Materials and Methods: This was a prospective comparative study. Altogether, 3015 prostate MRI reports incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…These findings substantiate the notion that the incorporation of prostate MRI reports alongside TNM staging offers valuable staging insights that can significantly contribute to informed clinical decision-making. In accordance with Zhang's [24] research, it was observed that urologists displayed a higher degree of satisfaction with reports incorporating TNM staging as opposed to reports containing solely PIRADS information.…”
Section: Should Radiologists Routinely Incorporate Tnm (Tumor Node Me...supporting
confidence: 77%
See 1 more Smart Citation
“…These findings substantiate the notion that the incorporation of prostate MRI reports alongside TNM staging offers valuable staging insights that can significantly contribute to informed clinical decision-making. In accordance with Zhang's [24] research, it was observed that urologists displayed a higher degree of satisfaction with reports incorporating TNM staging as opposed to reports containing solely PIRADS information.…”
Section: Should Radiologists Routinely Incorporate Tnm (Tumor Node Me...supporting
confidence: 77%
“…Beyond the imperative of diagnostic accuracy, clinicians place a premium on linguistic clarity in radiology reports [21,22]. Extensive research has consistently demonstrated that urologists prefer SR within the PIRADS framework [23,24]. The evidence presented here highlights the potential for structured reports to not only streamline reporting practices but also contribute to better patient outcomes, reduced variability in reporting, and improved training for new radiologists.…”
Section: Should Mri Reports Be Structured or Presented In Free-text F...mentioning
confidence: 81%